2020
DOI: 10.1039/d0ay00294a
|View full text |Cite
|
Sign up to set email alerts
|

Elemental chemical composition and As speciation in rice varieties selected for biofortification

Abstract: Toxic elements, essential elements and other elements were determined in Brazilian rice by inductively coupled plasma-mass spectrometry (ICP-MS). A method for As speciation using hydride generation was developed and applied in rice samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…In a study of As in rice from Brazil, total iAs was determined by ICP-MS (34.4 to 86.5 ng g À1 ), and then HPLC-HG-ICP-MS used to determine As III , As V , MMA and DMA with LOD values of 0.004 mg L À1 for DMA, 0.003 mg L À1 for MMA and As III and 0.010 mg L À1 for As V . 63 The mass balance, total of the As species compared with the total As content, for ten analysed samples were satisfactory in most cases, ranging from 90.1 to 127% with a mean of 107%, although recoveries were high for two of the samples (127% for Red Rice variety and 122% for "Marabá" variety). The mean percentages of As species in the ten rice varieties were 65% As III , 16% As V , 24% DMA and 12% MMA.…”
Section: Arsenicmentioning
confidence: 87%
See 1 more Smart Citation
“…In a study of As in rice from Brazil, total iAs was determined by ICP-MS (34.4 to 86.5 ng g À1 ), and then HPLC-HG-ICP-MS used to determine As III , As V , MMA and DMA with LOD values of 0.004 mg L À1 for DMA, 0.003 mg L À1 for MMA and As III and 0.010 mg L À1 for As V . 63 The mass balance, total of the As species compared with the total As content, for ten analysed samples were satisfactory in most cases, ranging from 90.1 to 127% with a mean of 107%, although recoveries were high for two of the samples (127% for Red Rice variety and 122% for "Marabá" variety). The mean percentages of As species in the ten rice varieties were 65% As III , 16% As V , 24% DMA and 12% MMA.…”
Section: Arsenicmentioning
confidence: 87%
“…The column effluent was mixed with a 65 Cu solution. Quantication of Cu-CDP in both fractions was performed by measuring the 63 Cu : 65 Cu isotope ratio although no mention is made of how mass bias was corrected for, if at all. Identication of Cu-CDP compounds was achieved by UHPLC-HR-MS. Around 13 Cu-CDC compounds were identied and quantied in the different types of table olives and the authors concluded that the ratio between Cu isochlorin e4 and Cu-15 2-Me-chlorin e6 could be applied to discriminate between table olives re-greened by processing with copper salts or with SCC.…”
Section: Coppermentioning
confidence: 99%
“…There were four reports of As speciation by HPLC with post-column HG in this review period. In a study of the elemental composition and As speciation in Brazilian rice varieties selected for biofortification, Freire et al 88 determined Al, As, Cd, Co, Cr, Fe, Mg, Mn, Ni, Rb, Sb, Sr and Zn by ICP-MS following microwave-assisted digestion. For As speciation, sample (0.2 g) was extracted with10 mL of 2% HNO 3 with heating from 25 to 95 °C (0.75 h) and holding at 95 °C for 1.5 h. After cooling, the extracts were filtered (0.20 μm cellulose) and 100 μL was injected for separation by anion-exchange HPLC (Hamilton PRP X-100, with 10 mmol L −1 phosphate buffer at pH 8.5 + 2% MeOH).…”
Section: Progress With Analytical Techniquesmentioning
confidence: 99%
“…In another study, 10 different varieties of Brazilian rice were tested for REEs, nutritional and toxic elements, and As species . 88 The speciation was carried out by HPLC-ICP-MS coupled with HG, which reduced LODs to 0.004 mg L −1 for DMA, 0.003 mg L −1 for MMA and As III and 0.010 mg L −1 for As V . Mean values across the 10 varieties of rice studied showed that iAs was the major species but all samples analysed had levels of As within the acceptable limits for infant consumption.…”
Section: Applications: Food and Beveragesmentioning
confidence: 99%
“…e determination methods of poly element contents in rice include an electrochemical method, atomic absorption spectroscopy (AAS) [22], atomic fluorescence spectrometry (AFS) [23], inductively coupled plasma optical emission spectrometer (ICP-OES) [24], and inductively coupled plasma mass spectrometry (ICP-MS) [25,26]. However, there are some common problems in these methods, which hamper the rapid determination of trace elements in rice, thus causing the reduction of the accuracy of traceability of multielement composition in rice.…”
Section: Introductionmentioning
confidence: 99%